Christian origins: Worship, belief, and society: The Milltown Institute and the Irish Biblical Association Millennium Conference - O'Mahony, Kieran J. (Great Britian, 2003)
This book looks at Christian origins under several headings: worship, belief, and society. The opening essay sets out to describe the immediate background of the early Christian movement within Judaism. The remaining nine essays look at how the early Christians worshipped, what did they believe about Jesus, and, finally, in what way did the early Christian movement come to social expression. The authors of the different essays are experts in their various fields.
Keywords: Judaism (Christian theology) -- History